Rancang Bangun Alat Pengendali Suhu pada Proses Pasteurisasi Susu Murni Menggunakan Arduino Berbasis IoT - Faulana, Nova; Budiarso, Zuly (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to design and develop a temperature control device for the pasteurization process of pure milk using Arduino based on the Internet of Things (IoT). The device is designed to monitor and regulate the temperature automatically during the pasteurization process to ensure its quality and safety. Arduino, as the main platform, is used to collect temperature data through temperature sensors that are directly connected to the system. The temperature data is then sent to a server through the internet network for real-time processing and monitoring. Intelligent temperature control algorithms are implemented in Arduino to adjust heating or cooling during the pasteurization process according to the set temperature point. The results of this research are expected to provide an efficient and accurate solution for temperature control in the pasteurization process of pure milk, as well as improve the overall safety and quality of dairy products.